2008
DOI: 10.2174/157017808786857589
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Phenyl Substituents on 13C NMR Shifts and Metal Ions Binding to 4-Phenyl-2,4-Dioxobutanoic Acid Derivatives

Abstract: Butanoic moiety of 4-aryl-2,4-dioxobutanoic acids is involved in interactions with metal ions within HIV-1 integrase active site. Sixteen congeneric 4-phenyl-2,4-dioxobutanoic acid derivatives with different substitution on the phenyl ring were prepared. Effects of substitution were studied by spectrometric methods (NMR, MS, UV/VIS) and linear free energy relationships. Better metal complexation ability of meta-alkyl substituted compounds, was observed. This observation might have pharmacological implications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
9
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 33 publications
0
9
0
Order By: Relevance
“…The synthesis and characterisation of 1-7, 13-19 was previously reported. [6,7] Characterisation data for 8-12…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The synthesis and characterisation of 1-7, 13-19 was previously reported. [6,7] Characterisation data for 8-12…”
mentioning
confidence: 99%
“…[10] We reported the influence of the phenyl substitution pattern in aryldiketo acids on Mg 2 + complexation. [7] In a similar manner, Mg 2 + bound to the fluoroquinolone carboxylic acid group at position 3 is necessary for the interaction with prokaryotic gyrase A (GyrA). [11] Furthermore, structural similarity between 1-20 and norfloxacin 21 was observed by overlaying the representative conformations of the monoanions of 1-20 generated by OMEGA, [12] with the representative conformations of 21 in its zwitterionic form, using ROCS.…”
mentioning
confidence: 99%
“…15 It was shown that 4-aryl-2,4-dioxobutanoic acids (aryldiketo acids, ADKs) exert promising activity against multidrug resistant bacteria. 16 Herein, as a continuation of work on structure-property relationship studies 17,18 and the biological activity of ADKs, 16 the effects of pH on electronic properties of nine congeners (compounds 1-9, Fig. 1) were investigated using cyclic voltammetry (CV), and differential pulse polarography (DPP).…”
Section: Introductionmentioning
confidence: 99%
“…It was shown that this moiety is responsible for the inhibitory activity of ADKs since it is involved in interactions with metal ions within active sites of target enzymes. 18 The substitution pattern on the phenyl ring was systematically varied, yielding a set having different torsion between phenyl ring and the aryl keto group (Ar-C(O)). Due to the presence of ortho-Me groups and tri-and tetra-Me-substitution at the phenyl ring for some compounds, different congeners most probably differently approach and interact with the electrode.…”
Section: Introductionmentioning
confidence: 99%
“…ADKs simultaneously exist in two enolate forms (Scheme 1, I and III), conformationally locked by the pseudo-ring, and one diketo form (II) having two rotatable bonds responsible for their conformational flexibility [15,17]. As a continuation of our group's work on structureproperty relationships [18][19][20] and biological activities of ADKs [6], we aimed to further explore their tautomeric preferences.…”
Section: Introductionmentioning
confidence: 99%